2020
DOI: 10.31224/osf.io/jdngb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new compressible hyperelastic model for the multi-axial deformation of blood clots occlusion in vessels

Abstract: Mechanical thrombectomy can be significantly affected by the mechanical properties of the occluding thrombus. In this study we provide the first characterization of the volumetric behaviour of blood clots. We propose a new hyperelastic model for the volumetric and isochoric deformation of clot. We demonstrate that the proposed model provides significant improvements over established models in terms of accurate prediction of nonlinear stress-strain and volumetric behaviours of low and high haematocrit clots. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In contrast, an isotropic hyperelastic formulation does not capture both compressive and tensile behaviour. This insight into the material model is an advance on our previous isotropic models [27,28], which were proposed based on only considering compression experiments. Also, the CZM modelling and J-integral analysis have only been used for a limited number of studies of biological soft tissues [52,53], and have not been used for blood clots before.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, an isotropic hyperelastic formulation does not capture both compressive and tensile behaviour. This insight into the material model is an advance on our previous isotropic models [27,28], which were proposed based on only considering compression experiments. Also, the CZM modelling and J-integral analysis have only been used for a limited number of studies of biological soft tissues [52,53], and have not been used for blood clots before.…”
Section: Discussionmentioning
confidence: 92%
“…In order to obtain detailed insights from the fracture tests described above, finite element simulations are performed in which crack initiation and propagation are predicted using a cohesive zone model. The clot material is modelled as an anisotropic hyperplastic fibrous soft tissue using the a recently proposed formulation [49] This formulation has been shown to accurately predict the isochoric and volumetric behaviour of blood clots over a wide range of clot compositions while facilitating control of unphysical auxetic behaviour [28]. The isochoric strain energy density function is given as…”
Section: Constitutive Modelling and Materials Parameters Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel material parameters are calibrated using published experimental stress-strain relationships for cranial vessels [21], resulting in the following It should be noted that the objective of the FSI simulation in this study is to demonstrate the capability of the developed platform and therefore these basic material models and parameters for the clot and artery are considered sufficient. More sophisticated material models such as those recently proposed for blood clots [23,24] and vessel walls [25] should be considered in future studies.…”
Section: Automated Fsi Model Creationmentioning
confidence: 99%
“…Development of improved design and simulation of aspiration thrombectomy devices is highly dependent on accurate modelling of the mechanical behaviour of blood clots. The authors recently developed hyperelastic constitutive model which have been shown to replicate the isochoric and volumetric deformation of thrombi during compression and tension tests (Fereidoonnezhad et al, 2021(Fereidoonnezhad et al, , 2020b. The main objective of the current paper is to incorporate permanent (unrecoverable) deformation, as reported in recent experimental investigations (Sugerman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%